Interpreting t-Statistics Under Publication Bias: Rough Rules of Thumb - Winship, Christopher (Journal of quantitative criminology, 2020)
A key issue is how to interpret t-statistics when publication bias is present. In this paper we propose a set of rough rules of thumb to assist readers to interpret t-values in published results under publication bias. Unlike most previous methods that utilize collections of studies, our approach evaluates the strength of evidence under publication bias when there is only a single study.